2015
DOI: 10.1021/acs.inorgchem.5b02077
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Ion Conductivity: Vapochromic Luminescence of an Ion-Conductive Ruthenium(II) Metalloligand-Based Porous Coordination Polymer

Abstract: We synthesized a new porous coordination polymer {La1.75(OH)1.25[Ru(dcbpy)3]· 16H2O} (La7-[4Ru]4; H2dcbpy = 4,4'-dicarboxy-2,2'-bipyridine) composed of a luminescent ruthenium(II) metalloligand [Ru(4,4'-dcbpy)3](4-) and La(3+) cations. X-ray analysis for La7-[4Ru]4 revealed that the La(3+) cations and [4Ru] metalloligands are crystallized in a molar ratio of 7:4 with OH(-) counteranions and a void fraction of ∼ 25.5%. Interestingly, La7-[4Ru]4 shows a reversible structural transition triggered by water ad/deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Absorption spectra showed that MOF exhibited efficient visible light harvesting with the absorption edge extended to around 650 nm due to the MLCT. The luminescence lifetime of MOF was 5.49 µs, which is more than one order of magnitude greater than that of [Ru] [234]. The coordination polymer exhibited a dark-red broad emission centered at 691 nm without any vibronic progressions, which is largely shifted to the longer wavelength than that of the 3 MLCT.…”
Section: Ligands Based On Highly Emissive Ruthenium(ii) and Iridium(iii) Complexesmentioning
confidence: 90%
“…Absorption spectra showed that MOF exhibited efficient visible light harvesting with the absorption edge extended to around 650 nm due to the MLCT. The luminescence lifetime of MOF was 5.49 µs, which is more than one order of magnitude greater than that of [Ru] [234]. The coordination polymer exhibited a dark-red broad emission centered at 691 nm without any vibronic progressions, which is largely shifted to the longer wavelength than that of the 3 MLCT.…”
Section: Ligands Based On Highly Emissive Ruthenium(ii) and Iridium(iii) Complexesmentioning
confidence: 90%
“…They have also found applications in novel solar cell functional materials [56], the reduction of carbon dioxide [57][58][59], etc. Additionally, inorganic chemists have utilized inorganic photocatalysts for functional components, viz, doping [60][61][62][63][64][65][66][67], encapsulated guests [68][69][70][71][72][73][74], molecular machines [75][76][77][78], for light harvesting, etc. [79].…”
Section: Review Why Photoredox Catalysis?mentioning
confidence: 99%
“…Since water molecules are generally contributable to the proton conduction in most of the low-temperature proton conductors in both the vehicle and Grotthus mechanisms, the incorporation of water-sensitive molecular luminophores could be an effective approach to evaluate the proton conductivity through the luminescence. We recently reported that the luminescent coordination polymers Ln 7 -[RuC] 4 , which are composed of Ru­(II) metalloligands functionalized with six carboxy groups, RuC (Scheme a; H 6 RuC = [Ru­(H 2 dcbpy) 3 ] 2+ ; H 2 dcbpy = 2,2′-bipyridine-4,4′-carboxylic acid), and bridging lanthanide cations (Ln 3+ = La 3+ , Ce 3+ , or Nd 3+ ) exhibit interesting relative humidity (RH)-dependent cooperative behavior between the ion conductivity and the 3 MLCT emission energy of the RuC metalloligand. , This system could be used as a smart sensor for the evaluation of ion conductivity via the 3 MLCT emission energy, but the ion conductivity is poor, even at 100% RH (ca. 10 –6 S cm –1 ), and the shift in the 3 MLCT energy is small.…”
Section: Introductionmentioning
confidence: 99%